EVENTCIBLE: The Planning Process for the Event Navigation and Tracking Mobile Application - Abdullah Azzam Syafrizal; Nurdiana Azizan; Noraizah Abu Bakar; Dini Onasis (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 2 Page (211-222)